IL-33-primed human mast cells drive IL-9 production by CD4+ effector T cells in an OX40L-dependent manner - Battut, Louise; Leveque, Edouard; Valitutti, Salvatore; Cenac, Nicolas; Dietrich, Gilles; Espinosa, Eric (Frontiers in Immunology, 2024)
is an alarmin released by epithelial cells in response to tissue damage. It activates resident immune sentinel cells, which then produce signals commonly associated with type 2 immune responses, particularly affecting infiltrating antigen-specific T cells. Given that mast cells (MCs) are a primary target of IL-33 and can shape T helper (Th) cell responses, we investigated the effect of IL-33 priming on the ability of MCs to influence Th cell cytokine production. To examine the Th cell/MC interaction, we developed human primary MC/memory CD4 + T cell coculture systems involving both cognate and non-cognate interactions. Our results demonstrated that IL-33-primed MCs, whether as bystander cells cocultured with activated effector T cells or functioning as antigenpresenting cells, promoted IL-9 and increased IL-13 production in Th cells via an OX40L-dependent mechanism. This indicates that MCs sense IL-33-associated danger, prompting them to direct Th cells to produce the key type 2 effector cytokines IL-9 and IL-13.with Th cells and influence their polarization. We showed that IL-33-primed MCs fostered Th2 cell responses and let emerge IL-9 producing Th cells in an OX40L-dependent manner.provide cues required by infiltrated Th cells to produce their cytokines and also signals that mold the panel of produced cytokine, here IL-9 and IL-13 via OX40-OX40L interaction.The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.